(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of hegemonic masculinity is defined as a practice that legitimizes men’s dominant position in society and justifies the subordination of the common male population and women another marginalized ways of being a man. My paper shows how the dominant man subjugates other men, women, and society. Reconstruction of hegemonic masculinity is crucial in the construction of nationhood. This research reveals that reconceptualisation or reconstruction of hegemonic masculinity with new formations of masculinity exist in opposition to existing ones and are healthier for men and less harmful for women. Contemporary hegemonic masculinity is built on two legs, domination of women and hierarchy of intermale domination. Postcolonial India has become obsolete and is in need of rejuvenation and rethought. I thought that masculine characteristics may help to built strong nationalism. How westerners had dominance over third world by their hegemonic masculinity, like that our Indian young male also inculcates those idealized hegemonic qualities in them. Such as courage, toughness, physical strength, athleticism, risk-taking, adventure, thrill seeking, competitiveness, achievement and success are dominant forms of masculinity is crucial in the construction of strong nationhood.